Electrical machine fundamentals with numerical simulation using MATLAB/SIMULINK - Iqbal, Atif; Moinoddin, Shaikh, 1954-; Reddy, Bhimireddy Prathap, 1993- (John Wiley & Sons, Inc., 2021)
"The book will focus on the basic understanding of the concept of electrical machines (working principles, equivalent circuit, and analysis) and will provide the simulation models of every type of machine described in the book. The book will elaborate on the fundamental concepts of electrical machines along with several numerical problems and simulation models using Matlab/Simulink."- Resumé vydavatele
Keywords: MATLAB (software); SIMULINK (software); elektrické stroje; electric machines; elektronické knihy; monografie; electronic books; monographs